KINERJA DITINJAU DARI KOMPETENSI, SUPERVISI PENGAWAS, PENGALAMAN KERJA, DAN LINGKUNGAN KERJA (Studi Pada Kepala SMP Negeri Kabupaten Sukoharjo) - Narya; Istiatin; Sudarwati (ITB AAS Indonesia Surakarta, 2025)
This study aims to test and analyze the influence of competency variables, supervisory supervision, work experience, and work environment. on the performance of the principal of Junior High School in Sukoharjo Regency. This research method uses a quantitative descriptive research design. The population is all principals of Junior High School in Sukoharjo Regency totaling 41 people. The sampling technique in this study is the census technique or saturated sample of 41 people. Data collection using a questionnaire and data analysis using SPSS 24.00 for calculating multiple linear regression analysis, F test, t test, and coefficient of determination. The results of the study indicate that competence, supervisor supervision, work experience, and work environment simultaneously and partially affect the performance of the principal, the higher the competence, supervisor supervision, work experience, and work environment, the better the performance of the principal. Based on the statistical test, the adjusted R square (R2) = 0.873 was obtained, meaning that the contribution of the variables competence, supervisor supervision, work experience, and work environment to the performance of the principal of SMP Negeri Sukoharjo Regency was 87.3% while the remaining 12.7% was influenced by other variables that were not studied, such as motivation, work discipline, and commitment.